Outdoor leadership theory and practice - Martin, Bruce 1969-; Breunig, Mary 1967-; Wagstaff, Mark 1959-; Goldenberg, Marni 1972- (Champaign, IL Human Kinetics, 2017)
Through lessons, activities, and exercises, Outdoor Leadership, Second Edition, will help students master eight core competencies essential to outdoor and adventure leadership, develop professional portfolios, and prepare to be successful leaders.
Part I Foundations of Outdoor Leadership : Chapter 1. The Journey Begins -- Chapter 2. History of Outdoor Leadership -- Chapter 3. Outdoor Leadership as Professional Practice -- Chapter 4. Cultural and Social Justice Competency in Outdoor Leadership ; Part II Outdoor Leadership Theory : Chapter 5. Theories of Leadership -- Chapter 6. Leadership in Practice -- Chapter 7. Decision Making and Judgment ; Part III Teaching and Facilitation : Chapter 8. Understanding Facilitation -- Chapter 9. Facilitating Personal Development -- Chapter 10. Facilitating Interpersonal Development -- Chapter 11. Challenge Course Leadership -- Chapter 12. Teaching Strategies ; Part IV Natural Resource and Program Management : Chapter 13. Parks and Protected Areas Management -- Chapter 14. Environmental Stewardship -- Chapter 15. Program Management -- Chapter 16. Safety and Risk Management -- Chapter 17. Expedition Planning -- Chapter 18. Assessment and Evaluation
Previous edition: 2006.
Includes bibliographical references and index.
Keywords: Recreation leadership; Outdoor recreation